Impact of Road Infrastructure and Foreign Direct Investment to Asean Economy - Dyah Maya Nihayah; Gilang Fajar Kurniawan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
In global economy era, developing countries try to increase their competitiveness. This study aims to analyze the effect of road infrastructure and Foreign Direct Investment (FDI) on Economic Growth as in ASEAN by 2008-2017. Variables in this research included economic growth, road length and FDI. The type of data used is panel data which analyzed by the Ordinary Least Square (OLS) method with fixed effect model specifications. The results showed that road infrastructure and FDI simultaneously had an effect for economic growth in ASEAN, and from the 9 countries the biggest effect is on Brunei Darussalam, Malaysia, and Thailand whose road infrastructure and FDI have a positive effect on economic growth in the period 2008-2017. Individually, road infrastructure variable has a negative effect, and FDI has a positive effect. It means that economic growth in ASEAN is less effected by physical capital and may be derived from other factors such as human resources or technological development, and investment has an important role in ASEAN economic growth. Further research is recommended to develop by adding other variables that are thought to have a relationship and represent the entire population.